The Influence of Knowledge, Religiosity, and Subjective Norms By Mediating Attitudes Towards The Purchase Intention of Halal Cosmetics - Putri Dewanti, Niken; Ridanasti, Erlita (International Journal of Social Research, 2024)
This research aims to determine the relationship and influence of knowledge, religiosity, and subjective norms with the mediation of attitudes on the intention to purchase halal cosmetic products. The data that will be presented in this research was obtained from the results of distributing questionnaires to 166 respondents from generation Y and Z Muslim consumers who consume halal cosmetic products in Indonesia. The sampling technique used in this research was non-probability sampling with a purposive sampling method. This research uses purposive sampling because special criteria are needed for the sample to be taken so that it can answer research problems and also provide representative values. Hypothesis testing in this research uses Structural Equation Modeling (SEM) analysis with the help of AMOS 24 software. The results of this research show that there is a positive and significant influence on the variables of knowledge, religiosity, subjective norms, attitudes and purchase intentions